Narrow-Beam Echo Sounding in Marine Geomorphology - Krause, D. C.; Kanaev, V. F. (The International Hydrographic Review, 2015)
The topography of the earth exists as a continuous spectrum in the scale of the features. Different scales require different methods of study. For deep-sea geomorphic studies, conventional echo sounding (wide-beam sounding) yields data from features on the scale of about one kilometre to features on the scale of the ocean basin. Deep-sea bottom photography yields data on the scale of millimetres to metres. This leaves a spectral gap of 1 - 1 000 metres about which, until recently, existed no satisfactory means of examination — yet this is the main scale on which terrestrial geomorphic interpretations are made. The information now available shows that this scale is equally as important to marine geomorphic interpretations. This paper will discuss the relationship of marine geomorphology and echo sounding. It will show how narrow-beam echo sounding yields unique data about the spectral gap of 1 - 1 000 metres necessary for geomorphic interpretation.